De Plagas Agrícolas en Trampa de Luz y Observaciones a Campo Del 2 al 8 de marzo de 2024 - Centeno, Alejandro René; Gasparetti, Graciela; Morano, Gonzalo Hector (AER San Francisco, INTA, 2025)
De Plagas Agrícolas en Trampa de Luz y Observaciones a Campo Del 2 al 8 de marzo de 2024.